KAJIAN PUSTAKA FAKTOR STRES KERJA, PERILAKU KESELAMATAN DAN SUPERVISI DENGAN KEJADIAN MINOR INJURY PADA SEKTOR KONSTRUKSI - Zhafira Revi Hanifah; Ida Wahyuni; Bina Kurniawan (Jurnal Kesehatan Masyarakat (Undip), 2020)
The implementation of the occupational safety and health management system is important to control the incidence of work accidents in a company. Work accidents are unexpected and undesirable events which can disrupt work process and work business. This study was aimed to analyze the relationship between job stresses, safety behaviour and supervisor with minor injuries in construction site. The method used in this research was the Literature Review Comparative Study. The literatures were conducted online through several trusted websites or internet sites such as Sciendirect, JSTOR, ProQuest, and Google Scholar.  This research was carried out on 15 articles consisting of 7 national articles and 8 international articles. Articles were analyzed bivariately and processed through stages in the form of editing, organizing, analyzing and disemination. The study concludes that the relationship between job stress and the minor accidents is stated to have a significant relationship, there is only one article that states the opposite. The relationship between safety behavior and supervision with minor accident events is concluded to have a very significant relationship that reviewed from all related articles.